Comparative study on selected species of aquaculture production in Malaysia under different agro-food incentive schemes - Ramzani, Sara Ravan (2014)
The aquaculture sector in Malaysia, like in most developing countries, plays an important role in the country’s economic development, functioning as food suppliers, employment creations, export earnings and raw material suppliers for other industries. It is believed that the superior taste of prawns and fishes, their high nutritional value and exceptional market shares are the reasons for their quickly developing in aquatic crustacean farming. The recent interest and development in aquaculture mostly due to several factors such as the growing demand for fish protein, limitations in production of capture fisheries, high production rate per unit area of aquaculture operations, less dependency on fuel, economic viability of aquaculture enterprises, ability to supply quality seafood, especially fresh and live aquaculture products. Cost of production appears to be one of the major factors likely to affect the future expansion of brackish water and fresh water farming in Malaysia. High cost of production due to increased cost of local labor and high cost of non-tradable inputs will eventually limit expansion and deteriorate the competitiveness of efficiency in the market. High per capita consumption in 2012 (54kg/year) may not be sustainable for the industry especially towards the already depleting fish stocks, and increase domestic price and production cost in 2012. Aquaculture business in Malaysia involves many fish farmers and commercial companies, practicing several types of production systems. However, they almost exclusively use unimproved species and strains. It seems that currently available knowledge and experience in aquaculture systems management are not being fully exploited to achieve sustained yield and optimum fish performance. The main objective of this study is to measure the comparative advantage and analyses policy protection in aquaculture production. The specific objectives are to calculate Policy Analysis Matrix (PAM) indicators and to rank the competitiveness of the three selected species ((Penaeus vannamei, Grouper and Barramundi) under different Agro-food incentive schemes. The study employed secondary and primary data gathered among 226 farmers, which was collected in 2012. The findings on the sustainability analysis of three main types of aquacultures productions namely brackish water species (Penaeus vannamei, Grouper and Barramundi) are discussed. This study provides a clear understanding on the current status of aquaculture in Malaysia and considers different aspects of government incentives for viable and sustainable aquaculture development. This research is in clouding of three sections. The first section discusses and provides the comparative analysis of the financial aspects of brackish water producers under different Agro-food incentives schemes. The financial analysis covers project evaluation criteria including, net present value (NPV), internal rate of return (IRR), and benefit cost ratio (BCR). The evaluation process was carried out using four different combinations of Agro-food incentives schemes: a) Base study and government incentives simulations, b) individually Pioneer status (PS), c) Investment Tax Allowance (ITA) and d) two combinations of PS and Accelerated Capital Allowance (ACA) and ITA and ACA. The results suggested that, in all brackish water farms, NPV after the ACA incentive showed a higher and positive value compared to individual PS and ITA. The Effect of Government Incentive on Penaeus vannamei and Grouper showed that IRR and NPV on ACA (based on PS) is 2% and 9%, respectively higher than ACA (based on ITA). Meanwhile in Barramundi ACA (based on ITA) was 8% higher than ACA (based on PS). This research concludes that in financial assessment, the aquaculture operators should choose to accept PS with ACA on Penaeus vannamei and Grouper, and choose ACA based on ITA on Barramundi, in order to maximize private profitability. The second section discusses and provides the findings of Policy Analysis Matrix (PAM) that provide information on economic analysis. The evaluation and discussion also deals with policy interventions evaluated by Nominal Protection Coefficient of Output (NPCO) and Nominal Protection Coefficient of Input (NPCI), and Effective Protection Coefficient (EPC). Meanwhile, the discussion on comparative advantage used ratios namely Domestic Resource Cost (DRC) and Social Cost Benefit (SCB). The finding of this study illustrate the analysis of private profitability which shows that brackish water species generate profit. The government interventions on aquaculture productions in terms of tax have a negative impact on the competitiveness on the selected species. On economic assessment, the PAM analysis results indicated that the brackish water species are economically profitable and competitive. In other words, producers used their resources efficiently with DRC and SCB ratios less than one. The competitiveness of brackish water species was ranked according to the Domestic Resource Cost (DRC), Social Cost Benefit (SCB) and Effective Protection Coefficient (EPC). The DRC, SCB and EPC indicates that Penaeus vannamei, have a high comparative advantage related to other species. Afterward Grouper is more comparative advantage and third is Barramundi. High comparative advantages in Penaeus vannamei is due to less input requirement and positive protected by government policy can be lead to lower production cost and increase the productivity. Section three presents the possible policy based simulations which highlight the effects of sensitivity analysis on financial and economic assessments. The result of sensitivity analysis showed that increase shadow exchange rate has great impact on comparative advantage. The level of competitiveness of brackish water production in Malaysia has improved when shadow price was used with government intervention devoted to subsidizing the brackish water factors of production.